The Use of SEO in Efforts to Increase Instagram Visitors at UD Bima Baru - Kala'lembang, Adriani; Rahayu, Widya Adhariyanty; Widayanti, Lilis; Fitria, Vivi Aida; Riska, Suastika Yulia (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research addresses increasing online sales competition and the use of SEO techniques, focusing on UD Bima Baru's Instagram. Method: This study employs a mixed-method research approach. The research design involves a combination of qualitative and quantitative elements to comprehensively investigate the impact of SEO techniques on online sales via Instagram. Data collection encompasses surveys, website traffic analytics, and content analysis of the Instagram account. Statistical analysis and content coding are utilized to derive meaningful insights from the collected data. Practical Applications: Our findings offer practical advantages, enhancing online visibility, engagement, and sales benefiting businesses across industries. Conclusion: This research highlights SEO's effectiveness in boosting visitor traffic and sales, offering actionable insights for thriving in the digital marketplace.